2016
DOI: 10.18632/aging.101048
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of long-noncoding RNA ZFAS1 is associated with epithelial-mesenchymal transition of gastric cancer

Abstract: LncRNAs play critical roles in gastric cancer (GC). In this study, the expression of fourteen cancer related lncRNAs were investigated in paired tissues of 66 patients with GC, Realtime RT-PCR revealed that ZFAS1 was significantly upregulated. We then examined the expression of ZFAS1 in plasmas derived from 77 GC patients before- and post-operations and 60 healthy individuals, and found that circulating ZFAS1 was also upregulated in GC patients and operation can reduce its presence in plasma. To investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 47 publications
0
61
0
Order By: Relevance
“…[6][7][8] For example, lncRNA LOC100129148 and EWSAT1 have been reported to act as oncogenic role in nasopharyngeal carcinoma, 9,10 lncRNA 00858 functions as a competing endogenous RNA for miR-422a to facilitate the cell growth in non-small cell lung cancer 11 and Increased expression of long-noncoding RNA ZFAS1 is associated with epithelial-mesenchymal transition of gastric cancer. 12 It also has been reported that high DLX6-AS1 expression levels were significantly associated with both histological differentiation and TNM stage of lung cancer. Down-regulation of lncRNA DLX6-AS1 expression decreased the DLX6 mRNA and protein levels.…”
Section: Introductionmentioning
confidence: 92%
“…[6][7][8] For example, lncRNA LOC100129148 and EWSAT1 have been reported to act as oncogenic role in nasopharyngeal carcinoma, 9,10 lncRNA 00858 functions as a competing endogenous RNA for miR-422a to facilitate the cell growth in non-small cell lung cancer 11 and Increased expression of long-noncoding RNA ZFAS1 is associated with epithelial-mesenchymal transition of gastric cancer. 12 It also has been reported that high DLX6-AS1 expression levels were significantly associated with both histological differentiation and TNM stage of lung cancer. Down-regulation of lncRNA DLX6-AS1 expression decreased the DLX6 mRNA and protein levels.…”
Section: Introductionmentioning
confidence: 92%
“…Recently, accumulating data demonstrated that non-coding RNAs (ncRNAs) are key regulators in both normal physiological and pathological conditions [5][6][7]. LncRNAs which are defined as those longer than~200 nucleotides, have been extensively characterized and it is evident that they are taking crucial roles in pathologies, including cancers [8][9][10][11][12][13]. In our previous study (GEO, http://www.ncbi.nlm.nih.…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNA ZFAS1 can be transferred by exosomes to promote gastric cancer progression, which suggests that ZFAS1 may be a diagnostic and prognostic biomarker for gastric cancer (22,23). Selective enrichment of the lncRNAs HOTAIR, HOX-AS-2, ANRIL, and linc-RoR in urinary exosomes from urothelial cancer patients was reported to be associated with poor prognosis (24,25).…”
Section: Discussionmentioning
confidence: 99%